Body mass index mediates the association between plasma lipid concentrations and the prevalence of obstructive sleep apnea among US adults: a cross-sectional study - Hu, Xiao; Xu, Jing; Gu, Yang (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe association between obstructive sleep apnea (OSA) and plasma lipid concentrations is not consistent. This study aimed to investigate the association of plasma lipid concentrations with the prevalence of OSA among US adults, with an additional examination of the mediating effect of body mass index (BMI).MethodsThis cross-sectional study included 8,086 individuals who participated in the National Health and Nutrition Examination Survey (NHANES), conducted from 2005 to 2008 and 2015–2018. Multivariable logistic regression analysis was conducted to compute the odds ratios (ORs) and 95% confidence intervals (CIs) for the association between plasma lipid concentrations and the prevalence of OSA. Additionally, subgroup analysis was used to explore the potential interactions. Generalized additive models (GAM) were constructed to evaluate the nonlinear relationships between lipid concentrations and OSA. Furthermore, mediation analysis was performed to assess the potential mediating role of BMI.ResultsIn the fully adjusted model, when comparing the lowest quartile, the ORs for the prevalence of OSA among participants in the highest quartile were 1.367 (95% CI, 1.107–1.688) for triglyceride and 1.212 (95% CI, 1.004–1.462) for low-density lipoprotein cholesterol (LDL-C). However, total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) were not associated with OSA. Notably, the relationship between triglyceride and OSA differed in the subgroups of gender, race, and body mass index (BMI) (P for interaction <0.05). Furthermore, we discovered an inverted U-shaped association between triglyceride and OSA (inflection point: 0.813 mmol/L). Causal mediation analysis revealed that BMI significantly mediated the relationship between triglyceride and the prevalence of OSA.ConclusionsThis study revealed that an elevated level of triglyceride increased the prevalence of OSA, and this effect was potentially mediated through BMI. Lowering triglyceride concentration may help to reduce the prevalence of OSA.